PENGARUH PENAMBAHAN SEKAM PADI DAN POLIMER EMULSI POLY VINYL ACECATE CO ACRYLIC PADA TANAH LEMPUNG DENGAN OBJEK PENGUJIAN KEKUATAN BATU BATA MENGGUNAKAN METODE UNIAXIAL - Halauddin, Halauddin (Inersia: Jurnal Teknik Sipil, 2017)
Research on the effect of the addition of rice husk and poly vinyl acetate emulsion polymer co acrylic (PVA) on clay have been conducted to see the strength of brick. Calculation of strength compared to brick by rice husks and polymer emulsion and given rice husk without any emulsion polymer. Provision of rice husk to batter was fixed at 9:1, while the provision of PVA polymer mixture for each batter with varying percentage are 1%-7%. Based on the results of the research, showed that: uniaxial compressive strength test resultsbricks to mix rice husk without PVA emulsion polymer was 28,7kg/cm2(L0), compressive strength test results bricks to mix rice husk with PVA emulsion polymer to a mixture of 1%-7%, respectively: (PVA 1% of 28,7 kg/cm2 (L1);(PVA 2% of 28,7 kg/cm2 (L2); (PVA 3% of 28,7 kg/cm2 (L3); (PVA 4% of 28,7 kg/cm2 (L4); (PVA 5% of 28,7 kg/cm2  (L5); (PVA 6% of 28,7 kg/cm2 (L6); and (PVA 7% of 28,7 kg/cm2 (L7). From the above results show that the compressive strength test results bricks to mix rice husk with PVA emulsion polymer mix increased from 1% to 3% mix, while starting from a mixture of 4% to 7% of the compressive strength of bricks dropped dramatically. The addition of PVA 3% of additions that the most effective way to improve the compressive strength of the bricks with compressive strength reached 53,5 kg/cm2, or increase of 46,4% from a brick with a mixture ofrice husk.